A simple plating assay for aneuploidy in sexual progeny of Neurospora crassa, and a new allele of mei-1. - A. T. Hagemann; J. T. Irelan; E. U Selker (Fungal Genetics Reports, 1997)
We developed a simple ascospore plating assay for aneuploidy, based on identifying disomic progeny that inherit two independently selectable mtr alleles. We validated the assay using a known meiotic mutant, mei-2. We used this assay to demonstrate that elevated frequencies of aneuploidy previously reported to be associated with reduced DNA methylation were not, in fact, due to the methylation deficiencies. A new allele of the mei-1 gene was responsible for some of the high aneuploidy.